A novel ratiometric fluorescent probe for rapid detection of hydrogen peroxide in living cells. Issue 67 (2nd December 2019) - Hu, Linan; Liu, Jiayi; Zhang, Jie; Zhang, Hailiang; Xu, Pengfei; Chen, Zhu; Xiao, Enhua
Abstract : A new ratiometric fluorescent probe JNY-1 for sensitive detection of H2 O2 is presented with selectivity over other reactive oxygen species, reactive nitrogen species, and biologically relevant species. Imaging of H2 O2 in liver cancer HepG2 cells was achieved. Abstract : In this work, we present a new ratiometric fluorescent probe JNY-1 for rapid and convenient detection of H2 O2 . The probe could selectively and sensitively respond to H2 O2 within 10 min. In addition, this probe was successfully applied for monitoring and imaging of H2 O2 in liver cancer HepG2 cells under physiological conditions.